The Integration-Interconnection Paradigm of UIN Sunan Kalijaga, M. Amin Abdullah's Perspective in Connecting Sharia and Natural Sciences - Rika Nurhidayah; Agus Wahyu Triatmo (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study discusses the integration-interconnection paradigm of UIN Sunan Kalijaga from the perspective of M. Amin Abdullah in connecting sharia and natural sciences. This study is motivated by the persistent dichotomy between religious and general sciences in Islamic education, so that a scientific framework is needed that is able to build a dialogue between religious texts, empirical reality, and philosophical reflection. This study uses a literature study method with a descriptive qualitative approach. Data were obtained from journal articles, books, and relevant scientific documents, then analyzed using content analysis techniques. The results of the study indicate that M. Amin Abdullah's integration-interconnection paradigm offers a complementary scientific relationship through three main frameworks, namely hadlarah an-nash, hadlarah al-‘ilm, and hadlarah al-falsafah. The spider web model or scientific spider web at UIN Sunan Kalijaga emphasizes that sharia and natural sciences are not positioned separately, but are interconnected in answering human problems in a complete and contextual manner. The implementation of this paradigm is evident in the development of curricula, learning, and scientific approaches that are informative, confirmatory, and corrective. While still facing challenges in terms of curriculum, faculty capacity, student readiness, and policy support, the integration-interconnection paradigm offers significant potential to strengthen Islamic higher education that is holistic, dialogical, and relevant to current developments.